Finite element analysis of a footing under combined loading - Kok, De Sheng (2018)
Other than vertical loading, shallow foundations also subjected to horizontal loading and overturning moment as a result of environmental loading (wave, wind), especially in offshore structures. The purpose of this study is to examine the stability of a footing in clay subjected to combined vertical, horizontal and moment loading using finite element analysis. A well-known geotechnical finite element analysis software, Plaxis is used to explore the failure curves of a footing under combined loading. Parametric studies are conducted to explore the failure envelopes of footings under combined loading with the effects of foundation shape and soil strength increasing with depth. Four types of footing (strip footing, rectangular footing, square footing and circular footing) are modelled using Plaxis 2D and Plaxis 3D. A case study is carried out to validate the ability of finite lement analysis to reproduce the actual result in real experiment. Mohr-Coulomb model is used throughout the whole research. The results for a footing subjected to combined vertical (V) and horizontal (H) loads in uniform soil presented in this study show that the maximum lateral load capacity does not occur at zero vertical load. In addition, for footing under combined vertical load and moment (M), the peak moment capacity occur about half of the maximum vertical load. While in footing under combined horizontal load and moment, the maximum moment capacity occur from positive horizontal load to negative horizontal with same direction of overturning moment when vertical load increases. On top of that, the failure envelopes of combined V-H and V-M loading in non-uniform soil do not share the same characteristics with the failure curves in uniform soil, particularly in low vertical load region. Both maximum horizontal load capacity and moment capacity occur at zero vertical load which is different from the results in uniform soil. In the case study, the results from finite element analysis are generally overestimated when compared to the actual test result from Martin’s (1994) experiment that show Mohr-Coulomb model in Plaxis 3D is not able to replicate the actual results from real experiment.